https://doi.org/10.36873/agp.v20: KARAKTERISTIK LAPISAN ACROTELM DAN CATOTELM PADA GAMBUT TRANSISI DAN PEDALAMAN The Characteristic of the Acrotelm and Catotelm on the Transition and Inland Peat, Turnip, S.U.1), Yulianti, N*1) dan Widiastuti, L1) - Admin journal (Fakultas Pertanian Universitas Palangka Raya, 2019)
ABSTRACTSince 1990s, the conversion of peatlands in Central Kalimantan from forest land cover and shrubs toagricultural land can cause the change of the characteristics of the peat. For this reason, this researchon the condition of peat properties is needed, especially the physical properties as a reference materialin the management of sustainable peatlands. This study was aims to determine the characteristics ofpeat under several land cover in the transition peat and the inland peat as well as the relationshipbetween the parameters. The research was conducted in September - December 2017, where located inWest Kanamit Village, Maliku Subdistrict and Taruna Jaya Village, Jabiren Raya Subdistrict, PulangPisau Regency, Central Kalimantan Province. The laboratory analysis at the Laboratory of Agronomyand the Laboratory of Analytical, University of Palangka Raya. Sampling in this study was uses aprofile with the size of one m2. This study was uses regression analysis and correlation methods thatare conducted to determine the pattern of relationships and the relationship between the variables ofthe physical properties of the peat. The results of the study indicate there is a similarity in the physicalproperties of the transition peat of West Kanamit Village and the inland peat of Taruna Jaya Village.The level of decomposition of peat from all locations was sapric with black to reddish black color. Theaverage values of the peat in West Kanamit Village are bulk density (0.09-0.18 g cm-3), water content(451.52-1,013.18%), fiber content (7.62-14.60%), ash content (1.73-26.15%), and organic C (42.83-57.00%). The results of the study in Taruna Jaya Village had the average values as follows as bulkdensity (0.10-0.17 g cm-3), moisture content (361.79-846.99%), fiber content (7.62-14.60 %), ashcontent (0.84-2.69%), and organic C (56.44-57.52%). Hydrophobicity in all study locations were 1.1-3.4 seconds with the WDPT method and the ratio of 0.06-0.49 with the FTIR methods. Moreover, therelationship between the peat characteristics shows a positive relationship and a negative relationship.Keyword : Acrotelm, Catotelm, Transition, Inland Peat